Potential impacts of the use of Trichoderma spp. on farmer's profit in the field control of club root disease of crucifers caused by Plasmodiophora brassicae Wor. - Cuevas, Virginia C. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2011)
Three farmer cooperators in Banooy, Buguias, Benguet used Trichoderma microbial inoculant (TMI) as a control measure against club root disease of crucifers caused by Plasmodiophora brassicae Wor., in addition to the usual farmers' practice of applying chemical pesticides. Two treatments were used: farmers' practice (FP - control) and T1 (Trichoderma inoculant). In both treatments, chicken manure (416 g m -2) and chemical fertilizers (triple 14, 205-220 g m -2) were applied; the chemical fungicide mancozeb (3.3 g m -2) and the insecticides carbaryl and flubendiamide (2.0 mL m -2) were also used. In T1, Trichoderma inoculant was applied at 0.5 g m -2 at the seedling stage, but not in FP. The test crops were Brassica oleracea capitata group (head cabbage) and B. rapa, Pekinensis group (Chinese cabbage). One farmer used less material and labor inputs in plots where Trichoderma inoculant was added; all other cultural practices were the same for both treatments. In all three farmers' fields, there was a very high incidence of the disease in the conventional plots where only chemical pesticides were used. In the conventional plots, all roots of diseased plants were clubbed - an indicator of full disease severity. In the plot treated with Trichoderma inoculant, disease incidence was reduced by 45%, indicating that only Trichoderma was able to control the disease. Roots of Trichoderma-treated infected plants showed suppression of the disease and production of new roots, allowing the continuous development of the crop and resulting in high yields. New infections were also prevented. Analyses of partial production cost and partial gross financial returns showed that Benguet farmers were losing as much as PhP 35,000 (∼ US$ 795) in 0.25-ha field per cropping due to ineffective control of the disease by chemical pesticides. The use of Trichoderma inoculant for disease control resulted in a three-fold increase in farmers' partial gross income.